Beroe gracilis (Ctenophora) from the Humboldt Current System: first occurrence of this species in the southern hemisphere - Oliveira, Otto M. P.; Feliú, Guillermo; Palma, Sergio (Zootaxa, 2014)
Beroe gracilis Künne, 1939 is a small neritic ctenophore, previously recorded only from cold waters of the northern hemisphere. The present study provides the first record of the species in the southern hemisphere, found in the surface layer of the Humboldt Current System off the central Chilean coast (32°–36.5° S). A complete description of this material is provided.